Selection of a new Pseudomonas chlororaphis strain for the biological control of Fusarium oxysporum f. sp. radicis-lycopersici - PUOPOLO, Gerardo; RAIO, Aida; PIERSON, Leland; ZOINA, Astolfo (Phytopathologia Mediterranea, 2011)
Fluorescent pseudomonads possess several physiological characteristics exploitable for the biological control of phytopathogenic fungi. A group of 11 pseudomonads able to inhibit tomato pathogenic fungi in vitro were identified using the Biolog test and the phylogenetic analysis of recA. Strain M71 of Pseudomonas chlororaphis was selected as a new potential biocontrol agent. This strain drastically reduced Fusarium oxysporum f. sp. radicis-lycopersici pathogenicity on tomato plantlets in seed assays and greenhouse trials. Moreover, the strain produced several important secondary metabolites, including proteases, siderophores and antibiotics. The presence of a region involved in phenazine production and the biosynthesis of N-acyl homoserine lactones were also assessed.